Dexmedetomidine Attenuates Ferroptosis-Mediated Renal Ischemia/Reperfusion Injury and Inflammation by Inhibiting ACSL4 via α2-AR - Tao, Wen-hui; Shan, Xi-sheng; Zhang, Jia-xin; Liu, Hua-yue; Wang, Bi-ying; Wei, Xiang; Zhang, Mian; Peng, Ke; Ding, Jun; Xu, Shang-xian; Li, Lin-gui; Hu, Jun-kai; et al. (Frontiers in Pharmacology, 2022)
Ischemia-reperfusion (I/R) injury is a serious clinical pathology associated with acute kidney injury (AKI). Ferroptosis is non-apoptotic cell death that contributes to renal I/R injury. Dexmedetomidine (Dex) has been shown to exert anti-inflammatory and organ protective effects. This study aimed to investigate the detailed molecular mechanism of Dex protects kidneys against I/R injury through inhibiting ferroptosis. We established the I/R-induced renal injury model in mice and OGD/R-induced HEK293T cell damage in vitro. RNA-seq analysis was performed for identifying the potential therapeutic targets. RNA-seq analysis for differentially expressed genes (DEGs) reported Acyl-CoA synthetase long-chain family member 4 (ACSL4) related to ferroptosis and inflammation in I/R mice, which was validated in rodent renal. Liproxstatin-1, the specific small-molecule inhibitor of ferroptosis, significantly attenuated ferroptosis-mediated renal I/R injury with decreased LPO, MDA, and LDH levels, and increased GSH levels. Inhibiting the activity of ACSL4 by Rosiglitazone (ROSI) resulted in decreased ferroptosis and inflammation, as well as reduced renal tissue damage, with decreasing LPO, MDA, and LDH levels, increasing GSH levels, reducing COX2, and increasing GPx4 protein expression, and suppressing the TNF-α mRNA and IL-6 mRNA levels. Dex as an α2-adrenergic receptor (α2-AR) agonist performed renal protective effects against I/R-induced injury. Our results also revealed that Dex administration mitigated tissue damage, inhibited ferroptosis, and downregulated inflammation response following renal I/R injury, which were associated with the suppression of ACSL4. In addition, ACSL4 overexpression abolishes Dex-mediated protective effects on OGD/R induced ferroptosis and inflammation in HEK293T cells and promotes ACSL4 expression by α2-AR inhibitor significantly reversing the effects on the protective role of Dex. This present study indicated that the Dex attenuates ferroptosis-mediated renal I/R injury and inflammation by inhibiting ACSL4 via α2-AR.